Study on overburden failure characteristics and displacement rule under the influence of deep faults - Zhang, Pei-Ding; Wu, Yong-Jiang; Cao, Zheng-Zheng; Li, Zhen-Hua; Du, Feng; Wang, Wen-Qiang; Zhai, Ming-Lei (Frontiers in Earth Science, 2024)
Deep faults have a significant impact on the structural stability and deformation behavior of overburden rock, which is a key factor in underground engineering and geological hazard research. Aiming at the problem of deep fault overburdened breaking during the mining of super thick coal seam, taking Yaoqiao Coal Mine as the research background, using numerical simulation and physical similarity simulation, the mining fracture evolution characteristics and overburden displacement law of non-structure and fault-bearing overburden corresponding to fully mechanized caving mining are compared and analyzed. The research results show that: (1) The fracture height of overlying rock presents a specific change law with the advance of the working face; the initial rapid increase to the maximum 74m, when the working face advances to 90m; and then with the development of the plastic zone indicating past yield, the fracture height decreases to 54m and becomes stable, and the final caving Angle of the fracture is stable at 70°. (2) In coal mining under normal fault conditions, when the working face is advancing from the upper wall to the lower wall, the roof forms a masonry beam structure, which slows down fault activation and crack development. When away from the fault, the overburden movement and water-conducting cracks are less, and the crack height is lower than that without faults. When approaching the fault, the influence of the fault on the fracture zone increases, and the height of the fracture development reaches the maximum after crossing the fault, which highlights the significant influence of the fault on the fracture development. (3) Through a similar simulation test, it can be seen that the overburden caving zone is further compacted by the overburden rock, and the roof collapses in a large range, resulting in the rapid upward development of the overburden rock cracks, and the separation of the central overburden rock cracks gradually compacted and closed. The research results have important theoretical and practical significance for deep underground engineering design, geological disaster prevention, and fault activity monitoring.